Experience of a workshop on communication skills in health professional education - Khalid U Al-Umran; Balachandra V Adkoli (Wolters Kluwer Medknow Publications, 2009)
Background: The teaching of communication skills is gaining increasing attention. However, the opportunities for faculty development are limited. This study highlights an attempt by the Medical Education Unit, King Fahd Hospital of the University, Al-Khobar, to raise the awareness of faculty to this vital area by organizing a one-day workshop. Method: A one-day workshop was organized to improve the awareness of the participants to the role of communication skills such as doctor-patient interaction, breaking bad news, counseling and conflict management. In all, 168 participants consisting of faculty members, interns and students, both male and female participated. The sessions included interactive lectures, video demonstrations and role play. Results: The feedback from the participants indicated that the objectives of the workshop were largely realized. The presentations by speakers were of high quality. However, the participants wanted more small group activities and video-demonstrations that were relevant to the local environment. Conclusion: By and large, the one-day workshop was found to be a practical model for an initial attempt to raise awareness. Further work is needed to organize more intensive workshops on specific issues related to communication skills.